Design considerations for aural vital signs using PZT piezoelectric ceramics sensor based on the computerization method - Suranan Noimanee (2018)
The purpose was to illustrate how system developed for measurement of the aural vital signs such as patient's heart and lung sounds in the hospital. For heart sounds measurement must operate the frequency response between 20 - 800 Hz, and lung sounds measurement must operate the frequency response between 160 - 4,000 Hz. The method was designed PZT piezoelectric ceramics for both frequency response in the same PZT sensor. It converts a signal from aural vital sign form to voltage signal. The signal is suitably amplified and re-filtered in band pass frequency band. It is converted to digital signal by an analog to digital conversion circuitry developed for the purpose. The results were that all signals can fed to personal computer through the sound card port. With the supporting software for drawing of graphic on the screen, the signal for a specific duration is accessed and stored in the computer's memory in term of each patient's data. In conclusion, the data of each patient call dot pcg (.pcg) for drawing graph and dot wave (.wave) for sound listening or automatic sending via electronic mail to the physician for later analysis of interpreting the sounds on the basis of their time domain and frequency domain representation to diagnose heart disorders. © 2007 by MDPI.